Colchicine increases intestinal toxic load by disturbing fecal metabolome homeostasis in mice. (1st December 2022) - Shi, Yongpeng; Li, Jiande; Wang, Ji; Cao, Hanwen; Tian, Huanbing; Yu, FeiFei; Gao, Lan
Abstract: Colchicine (COL) has been used to treat gout for over a millennium, but its medicinal use has been controversial due to its potent toxicity in the gastrointestinal tract. Nausea, vomiting, and diarrhea are the most prominent external manifestations of COL gastrointestinal toxicity, but the cause of these adverse events remains obscure. In this study, the mice were exposed to COL (2.5 mg/kg b.w./day) for one week to study the mechanism of COL-induced diarrhea from the perspective of intestinal metabolism. The results showed that COL exposure disturbed intestinal metabolic homeostasis, resulting in a significant accumulation of 116 metabolites and, conversely, significant depletion of 64 metabolites, with the number of differential metabolites being one-eighth of the total metabolites (180/1445). Also, it was found that cAMP, Adenosine 5′-monophosphate, GDP, Inositol, and Cortisol are core metabolites that play crucial roles in COL-induced metabolic disorders. These metabolites could be used as biomarkers to differentiate control and COL-treated groups, implying that these metabolites may be closely related to COL-induced diarrhea. Furthermore, changes in the metabolic pathways (Purine metabolism, biosynthesis and metabolism of aromatic amino acids, and Bile secretion) involved in these five core metabolites increased the toxic load in the gut, which was the culprit leading to intestinal metabolic disorders. In addition, the abnormal bile secretion caused by COL exposure may play an important role in COL-induced diarrhea. In conclusion, our study opens new avenues for understanding the mechanisms of COL-induced gastrointestinal adverse reactions and broadens the scientific horizon on the interactions between COL and host metabolism. Highlights: COL exposure caused metabolic disturbances in mice. The floating of core metabolites is a vital cause of metabolic disorders in mice. Abnormal bile secretion plays a crucial role in COL-induced diarrhea. This is an important study to elucidate the mechanism of COL gastrointestinal toxicity.